Research on particle collision forward search algorithm and CFD–DEM variable time step coupling calculation method - Wang, Xuefei; Wang, Suling; Wang, Ming; Li, Xuemei; Sun, Dandan; Su, Chen (Acta mechanica, 2022)
In CFD–DEM coupling calculation, the calculation accuracy will decrease if the particle calculation time step is too large, while the calculation efficiency will decrease if the particle calculation time step is too small. In this study, first, the displacement of the center particle and the fastest particle in the computational domain is added to construct a search sphere. Subsequently, the particles that may collide are screened to create a search list, and particle collisions are determined using a forward search method. Finally, an improved DEA method is proposed; the time step of particle calculation is automatically adjusted according to the collision time, which solves the contradiction between selecting particle calculation time step, accuracy, and efficiency. The relative error between the particle collision simulation results and the analytical solution obtained by this method is less than 3.00%. In this study, three selected calculation time steps can ensure excellent calculation accuracy and efficiency. In multi-particle and fluid coupling simulation analysis, when the calculation time step is 10 –5 s, the calculation efficiency is improved by 19.8%.